Organellar-genome analyses from the lycophyte genus Isoetes L. show one of the highest frequencies of RNA editing in land plants - Pereira, Jovani Bernardino de Souza; Oliveira, Renato Renison Moreira; Vasconcelos, Santelmo; Dias, Mariana Costa; Caldeira, Cecı́lio Frois; Quandt, Dietmar; Oliveira, Guilherme; Prado, Jefferson (Frontiers in Plant Science, 2024)
RNA editing is a post-transcriptional process that challenges the central dogma of molecular biology by modifying RNA sequences, introducing nucleotide changes at specific sites, and generating functional diversity beyond the genomic code, especially when it concerns organellar transcripts. In plants, this phenomenon is widespread, but its extent varies significantly among species and organellar genomes. Among land plants, the heterosporous lycophytes (i.e., Isoetes and Selaginella) stand out for their exceptionally high numbers of RNA-editing sites, despite their morphological stasis and ancient lineage. In this study, we explore the complete set of organellar protein-coding genes in the aquatic plant group Isoetes, providing a detailed analysis of RNA editing in both the mitochondrial and plastid genomes. Our findings reveal a remarkable abundance of RNA editing, particularly in the mitochondrial genome, with thousands of editing sites identified. Interestingly, the majority of these edits result in non-silent substitutions, suggesting a role in fine-tuning protein structure and function. Furthermore, we observe a consistent trend of increased hydrophobicity in membrane-bound proteins, supporting the notion that RNA editing may confer a selective advantage by preserving gene functionality in Isoetes. The conservation of highly edited RNA sequences over millions of years underscores the evolutionary significance of RNA editing. Additionally, the study sheds light on the dynamic nature of RNA editing, with shared editing sites reflecting common ancestry whereas exclusive edits matching more recent radiation events within the genus. This work advances our understanding of the intricate interplay between RNA editing, adaptation, and evolution in land plants and highlights the unique genomic features of Isoetes, providing a foundation for further investigations into the functional consequences of RNA editing in this enigmatic plant lineage.